Comparing Transcriptomes Reveals Key Metabolic Mechanisms in Superior Growth Performance Nile Tilapia (Oreochromis niloticus) - Chen, Binglin; Xiao, Wei; Zou, Zhiying; Zhu, Jinglin; Li, Dayu; Yu, Jie; Yang, Hong (Frontiers in Genetics, 2022)
Metabolic capacity is intrinsic to growth performance. To investigate superior growth performance in Nile tilapia, three full-sib families were bred and compared at the biochemical and transcriptome levels to determine metabolic mechanisms involved in significant growth differences between individuals under the same culture environment and feeding regime. Biochemical analysis showed that individuals in the higher growth group had significantly higher total protein, total triglyceride, total cholesterol, and high- and low-density lipoproteins, but significantly lower glucose, as compared with individuals in the lower growth group. Comparative transcriptome analysis showed 536 differentially expressed genes (DEGs) were upregulated, and 622 DEGs were downregulated. These genes were significantly enriched in three key pathways: the TCA cycle, fatty acid biosynthesis and metabolism, and cholesterol biosynthesis and metabolism. Conjoint analysis of these key pathways and the biochemical parameters suggests that Nile tilapia with superior growth performance have higher ability to convert energy substrates (e.g., glucose) to ATP, as well as higher ability to biosynthesize fatty acids and cholesterol. Additionally, the fatty acids biosynthesized by the superior growth performance individuals were less active in the catabolic pathway overall, but were more active in the anabolic pathway, and might be used for triglyceride biosynthesis to store excess energy in the form of fat. Furthermore, the tilapia with superior growth performance had lower ability to convert cholesterol into bile acids, but higher ability to convert it into sterols, which may provide more substrate for adrenal cortex hormones and sex hormones to promote development of the tilapia reproductive system and the growth of bone and muscle. We discuss the molecular mechanisms of the three key metabolic pathways, map the pathways, and note key factors that may impact the growth of Nile tilapia. The results provide an important guide for the artificial selection and quality enhancement of superior growth performance in tilapia.